No Choice but to Be Essential: Expanding Dimensions of Precarity During COVID-19. (October 2021) - Loustaunau, Lola; Stepick, Lina; Scott, Ellen; Petrucci, Larissa; Henifin, Miriam
Under COVID-19, low-wage service sector workers found themselves as essential workers vulnerable to intensified precarity. Based on in-depth interviews with a sample of 52 low-wage service workers interviewed first in Summer 2019 and then in the last two weeks of April 2020, we argue that COVID-19 has created new and heightened dimensions of precarity for low-wage workers. They experience (1) moments of what we call precarious stability, in which an increase in hours and predictable schedules is accompanied by unpredictability in the tasks workers are assigned, (2) increased threats to bodily integrity, and (3) experiences of fear and anxiety as background conditions of work and intensified emotional labor. The impacts of COVID-19 on workers' lives warrant an expanded conceptualization of precarity that captures the dynamic and shifting nature of precarious stability and must incorporate workers' limited control over their bodily integrity and emotions as core components of precarious working conditions.